Study of safety and efficacy of autologous platelet rich plasma combined with fractional CO2 laser in the treatment of post acne scars: a comparative simultaneous split-face study - Shah, Sidhartha D.; Mehta, Bipin D.; Borkar, Milind A.; Aswani, Reshma C. (International Journal of Research in Medical Sciences, 2017)
Background: Many treatments are available for treating post acne scars but optimized treatment does not exist still. Hence, this study was conducted with the aim to evaluate the safety and efficacy of autologous platelet rich plasma combined with fractional CO2 laser for treatment of acne scars when used in Indian skin. Methods: Thirty patients attended to the Dermatology OPD were enrolled in the study after meeting inclusion criteria. They underwent split-face therapy. They received ablative fractional carbon dioxide (CO2) laser combined with autologous platelet-rich plasma (PRP) treatment on one half of their face and ablative fractional CO2 laser with intradermal normal saline on the other half. The injections were administered immediately after laser therapy. Each participant received 4 treatments spaced by 1 month and were followed up for a period of 4 months. Results: The outcome among the study subjects were assessed using Goodman and Baron Scale at different time intervals. Significant reduction in acne scars was observed in both PRP injection site and normal saline injection site but better reduction of acne scars was noted at the PRP site. The blinded physician’s assessment and patient satisfaction was better at PRP injected side as compared to the normal saline injected side. The incidence of adverse effects and pain during the procedure was significantly lower in PRP injected side compared normal saline injected side. Conclusions: This study demonstrated that PRP should be considered as an adjuvant therapeutic option for dermatologic procedures such as fractional CO2 laser resurfacing for treatment of post acne scars as it might have additional benefit of reducing the adverse effects such as persistent erythema and edema.